Public administration and the colonial administrator - Kirk-Greene, Anthony (1999)
By title, function and history, the colonial administrator was prima facie an early example of the professional administrator. Yet how far public administration was an integral element in his training and performance is questionable. By the decolonizing 1950s, public administration was still not a conspicuous feature in the administrative vocabulary. Even when the latter-day colonial administrator was subjected to the educating influence of the Journal of African Administration, neither he nor the Journal widely resorted to the use of public administration pur sang. Yet administrative training was the keyword for both. This article directs attention to the way in which colonial administrators were selected and how they were trained. Three critical, post-1950, influences on the latter-day colonial administrator are examined: the impact of the Journal of African Administration; the role and staffing of Africa's new Institutes of Administration; and the colonial administrator's `second career' in public administration in the U.K. - Reproduced
Keywords: Public administration